Analisis Faktor Penyebab Pernikahan Dini Pada Remaja Di Desa Mentajoi Kecamatan Serawai Kabupaten Sintang - Devi, Friska; Imran, Imran; Ramadhan, Iwan (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
The purpose of this study was to determine the factors causing early marriage in Mentajoi Village, Serawai District, Sintang District, and the impact of early marriage. The research approach used is a qualitative approach with descriptive methods. Data collection techniques are interviews and documentation. The data collection tool used was a combination of interviews and documentation. The data analysis techniques used were data reduction, data presentation, and conclusion drawing. This study indicates that the occurrence of early marriage in Mentajoi Village is caused by two factors, namely internal and external factors. The internal factor is having made a biological relationship and the factor of education. External factors are caused by parents, namely parental education that is low so that they are submissive and lack supervision, and cultural customs factors, namely violating customary law. The impact of early marriage is the obstruction of freedom of expression in looking for work in an economy, difficulties in fulfilling needs, dropping out of school, which makes it difficult to find work.